Fertility and other stories - Ivanov, Vsevolod Viacheslavovich, 1895-1963 (Sources and translations series of the Harriman Institute, Columbia University, 1998)
Vsevolod Ivanov was praised in the 1920s as one of the most original and promising young writers to emerge from the Russian Revolution. Ivanov's personal experiences in Siberia and Central Asia during the Revolution and Civil War, set against a childhood and youth spent wandering through that vast expanse and nourishing his imagination on such Romantic writers as Edgar Allan Poe and Jules Verne, infuse his writing. Combining traditional elements with the fantastic and the surreal, Ivanov's stories address not only the themes of the Revolution - the dehumanizing effects of famine; the ferment, energy, and uncertainty of the tempestuous times - but also the quotidian: the quiet world of man and nature, and the elemental bond that tied peasants to their native land.